Comparison of Exercise Programs With and Without the Use of the Ball for the Improvement of the Maximum Speed, the Speed Endurance and the Countermovement Jump in Young Football Players 14-15 Years Old - Zafeiriou Παναγιώτης; Christoforidis Χρήστος; Kampas Αντώνης; Douroudos Ιωάννης; Taxildaris Κυριάκος (Inquiries in Physical Education and Sport, 2007)
The purpose of this research was to find the effects from the application of exercise programs, with and without the use of the ball, in speed, in speed endurance and in squat jump on 120 amateur football players 14-15 years old. The young subjects were divided randomly into three groups of 40 players each: a) experimental training group with ball (EG-B), b) experimental training group without ball (EG) and c) control group (CG). Initial and final measurements were took place for the evaluation of the maximum speed (sprint 40m), the speed endurance (6x40m) and the countermovement jump. Between the tests, exercise programs were applied with total duration of 15 weeks and frequency three times per week. The heart rate was recorded during the test of maximal speed, while the heart rate and the concentration of the lactic acid were recorded during the endurance the test. For the statistical treatment of the data a Two-way Analysis of Variance (ANOVA) with Repeated Measures was used. Results showed statistically significant improvement, between the initial and the final test, in both experimental groups in maximal speed (p<.001), speed endurance (p<.001), heart rate in the tests of maximal speed (p<.001) and speed endurance (p<.001) and in lactic acid concentration in the speed endurance test (p<.001), but no improvement was found in countermovement jump. As far as concern the effect of the variable group, statistically significant differences were found in the final measurements, between 1st-3rd and 2nd-3rd in the aggregate of the variables (p<.001), with the exception of the countermovement jump. In conclusion it was found that systematic speed training may improve the maximum speed and the endurance speed and reduce the levels of the heart rate and the lactic acid concentration, but has no significant effects on countermovement jump.